2022
DOI: 10.1111/cdev.13761
|View full text |Cite
|
Sign up to set email alerts
|

The role of harsh parenting practices in early‐ to middle‐childhood socioemotional development: An examination in the Millennium Cohort Study

Abstract: role of harsh parenting practices in early-to middlechildhood socioemotional development: An examination in the Millennium Cohort Study', Child Development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 77 publications
0
8
2
4
Order By: Relevance
“…In particular, parental involvement was associated with increases in externalising problems whereas harsh parenting was associated with decreases in internalising problems. Prior research has suggested that coercive family processes are associated with an escalation of both internalising and externalising difficulties (Patterson, 2002;Speyer et al, 2022), whereas our findings using parent-reported data on internalising and externalising problems suggested the opposite effect. Considering that we did not observe the same associations in the teacher-reported model, one reason for these findings may be that parents using harsh parenting techniques may be less perceptive of their child's internalising difficulties and thus underreport their emotional problems, whereas parents who are very involved in their children's lives may overreport instances of externalising behaviours as they are very attuned to their child's behaviour.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, parental involvement was associated with increases in externalising problems whereas harsh parenting was associated with decreases in internalising problems. Prior research has suggested that coercive family processes are associated with an escalation of both internalising and externalising difficulties (Patterson, 2002;Speyer et al, 2022), whereas our findings using parent-reported data on internalising and externalising problems suggested the opposite effect. Considering that we did not observe the same associations in the teacher-reported model, one reason for these findings may be that parents using harsh parenting techniques may be less perceptive of their child's internalising difficulties and thus underreport their emotional problems, whereas parents who are very involved in their children's lives may overreport instances of externalising behaviours as they are very attuned to their child's behaviour.…”
Section: Discussioncontrasting
confidence: 99%
“…Two parental factors that may be particularly relevant in mediating developmental cascades are harsh parenting and parental involvement. Many studies have suggested that harsh parenting practices lead to increased behavioural problems (for a review, see Gershoff, 2002;Pinquart, 2017a) with research further pointing to internalising problems as an outcome of the coercive parent-child interaction cycle proposed by Patterson (Dallaire et al, 2010;Pinquart, 2017b;Speyer et al, 2022). Other research has further suggested that parental involvement may be relevant in the development of both externalising and internalising problems (Aboobaker et al, 2019;Hawes et al, 2013;Kirkhaug et al, 2013).…”
mentioning
confidence: 99%
“…In particular, parental involvement was associated with increases in externalising problems whereas harsh parenting was associated with decreases in internalising problems. Prior research has suggested that coercive family processes are associated with an escalation of both internalising and externalising difficulties (Patterson, 2002;Speyer et al, 2022), whereas our findings using parent-reported data on internalising and externalising problems suggested the opposite effect. Considering that we did not observe the same associations in the teacher-reported model, one reason for these findings be that parents using harsh parenting techniques may be less perceptive of their child's internalising difficulties and thus underreport their emotional problems, whereas parents who are very involved in their children's lives may overreport instances of externalising behaviours as they are very attuned to their child's behaviour.…”
Section: Discussioncontrasting
confidence: 99%
“…As this cycle continues, the frequency and intensity of these behaviors increase significantly as parents and children are reinforced for their coercive responses. These coercive parent-child interactions have been documented in numerous studies during infancy, toddlerhood, preschool, and the early school years (e.g., Martin, 1981;Shaw et al, 1994Shaw et al, , 1998Slep et al, 2018;Smith et al, 2014;Speyer et al, 2022).…”
Section: Coercion Theory: An Overviewmentioning
confidence: 99%